SOME INSIGHTS INTO WEIGHTED IDEAL STATISTICAL CONVERGENCE OF FUZZY VARIABLES IN CREDIBILITY SPACES - Kişi, Özgür; Akbıyık, Rümeysa; Gürdal, Mehmet (Palestine Polytechnic University, 2025)
This paper investigates different forms of weighted ideal statistical convergence for double sequences of fuzzy variables within the framework of credibility. Furthermore, illustrative examples are provided to analyze the relationships among these fuzzy variable double sequences. Lastly, the concept of a weighted ideal statistically Cauchy sequence of fuzzy variable double sequences is introduced to establish its connection with weighted ideal statistically convergent fuzzy variable double sequences. © Palestine Polytechnic University-PPU 2025.
Keywords: credibility; fuzzy variable; Ideal Statistical Convergence; weighted